2013
DOI: 10.1128/jcm.02441-13
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity, Specificity, and Reproducibility of the Capilia TB-Neo Assay

Abstract: bThe performance of the Capilia TB-Neo assay, a new-generation assay, was assessed by determining its sensitivity, specificity, reproducibility, and cross-reaction with contaminating organisms. The sensitivity and specificity were 99.2 and 96.4% and 89.3 and 100% in pure and mixed-culture isolates, respectively. The kappa statistic was 95.0 and 77.9% in pure and mixed culture isolates, respectively. There was no cross-reaction with contaminating organisms. The Capilia TB assay is a rapid, simple, and inexpensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…[3][4][5] Consistent with previous reports, the Capilia TB-Neo assay demonstrated a specificity of 100%. 7,11 We observed a sensitivity of 97%, higher than reported by Gomanthi et al but similar to that reported by Muyoyeta et al and lower than those reported by Pokam et al and Chikamatsu et al 6,7,11,12 Reactivity with NTM such as M. avium, M. kansasii, M. fortuitum, M. gordonae, M. chelonae, M. peregrinum and other micro-organisms, such as Nocardia spp., K. pneumoniae, P. aeruginosa, E. coli, S. aureus, C. albicans and P. mirabilis, was checked and a cross-reaction was confirmed as absent for all of these as well as for the negative cultures tested. Although we detected no false-positive results, we did detect three false-negative results.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[3][4][5] Consistent with previous reports, the Capilia TB-Neo assay demonstrated a specificity of 100%. 7,11 We observed a sensitivity of 97%, higher than reported by Gomanthi et al but similar to that reported by Muyoyeta et al and lower than those reported by Pokam et al and Chikamatsu et al 6,7,11,12 Reactivity with NTM such as M. avium, M. kansasii, M. fortuitum, M. gordonae, M. chelonae, M. peregrinum and other micro-organisms, such as Nocardia spp., K. pneumoniae, P. aeruginosa, E. coli, S. aureus, C. albicans and P. mirabilis, was checked and a cross-reaction was confirmed as absent for all of these as well as for the negative cultures tested. Although we detected no false-positive results, we did detect three false-negative results.…”
Section: Discussionsupporting
confidence: 86%
“…The existence of false-negative results on Capilia TB-Neo was not further evaluated, but it may have been due to one of the following reasons: either the mpb64 gene was deleted, as previously reported for some Evaluation of the Capilia TB-Neo assay BCG strains, such as substrains of the Pauster and Glaxo strains, 7,13 or the mpb64 gene was mutated, leading to the production of an incomplete protein. 6,7 Despite the false-negative results, we found the sensitivity of the Capilia TB-Neo to be similar to that observed for AccuProbe (96.8%). 14 Unlike the molecular method, the IC test is a rapid one-step test (15 min after positivity of cultures), that is less expensive and does not require sample preparation, trained technicians or sophisticated equipment.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The Capilia TB-Neo assay is a second-generation test that eliminated previous cross-reactions with certain NTM and nonmycobacterial bacteria to improve specificity (210). Due to mutations (most commonly due to a 63-bp deletion at position 196) in the gene encoding MPB64, the test gave false-negative results for some M. bovis BCG and, more recently, M. africanum variants (211)(212)(213).…”
Section: Lateral Flow Assaysmentioning
confidence: 99%
“…Several factors have been shown to impact the results of IGRAs (206)(207)(208)(209)(210)(211)(269)(270)(271)(272)(273)(274). Preanalytical factors such as the amount of time from blood collection to incubation can significantly affect IGRA results (269).…”
Section: Use Of Interferon Gamma Release Assays For Diagnosis Of Mycomentioning
confidence: 99%